The role of middle powers in the Pacific : Indonesia-Canada relations towards the year 2000 - Centre for Strategic and International Studies (Jakarta : Centre for Strategic and International Studies, 1985)
Indonesia-Canada Conference. 1st, February 4-6, 1985, Bali
Keywords: Canada -- Foreign relations -- Indonesia; Indonesia -- Foreign relations -- Canada